The Impact of Citizen Journalism on Mainstream Media Reporting: A Pakistani Journalists' Perspective - Mahmood, Dr. Qasim; Qureshi, Iqra; Dr. Rao Nadeem Alam (Journal of Peace, Development and Communication, 2023)
Citizen journalism has been studied in the past and has become a popular trend in the present era. There is a rising concern about the increasing popularity of citizen journalism and its impact on mainstream media reporting. The study discusses this concern by using a theoretical lens of ‘Public Sphere’ which helps to understand the contribution of citizen journalism in the democratic process. A convenient sampling method has been used and semi-structured interview were conducted by 10 journalists of mainstream media. Thematic analysis procedure has been adopted to draw the findings from the collected data. The findings of the study were measured based on relevance of answers given by the journalists with the research objectives. The results of the study address the objectives of the study and the findings expressed how citizen journalism impacts mainstream media reporting. The study’s practical implications include awareness of the concern for the general news audience, citizen journalists and mainstream media.